The Protective Effect of Amino Acids on the Copper(II)-Catalyzed Autoxidation of Ascorbic Acid - (:unkn) unknown (FOOD & DRUG ADMINSTRATION, 2008)
Protection of ascorbic acid (AA: vitamin C) from Cu(II)-catalyzed autoxidation is an important aspect of antioxidant chemistry. The autoxidation of AA in the absence and presence of Cu(II) ions was investigated in aerated solution at room temperature and I = 0.1 ionic strength (KNO3). Effects of eight biochemically important amino acids (alanine, glycine, aspartic acid, asparagine, glutamic acid, glutamine, phenylalanine, and histidine) on this system were studied. The concentration of unoxidized AA remaining in solution was measured with the CUPRAC (cupric ion reducing antioxidant capacity) spectrophotometric method without interference from the amino acids tested. The autoxidation rate constants of AA decreased with increasing amino acid concentration for fixed Cu, and increased with Cu(II) for fixed amino acid concentrations. Catalytic autoxidation of AA was inhibited by stable Cuamino acid complexes; histidine, having the highest conditional stability constant for its Cu-complex, showed the strongest inhibitive effect. Since amino acids are food and drug compatible compounds, they can be used in commercial products to increase the stability of vitamin C.
Keywords: ascorbic acid; vitamin C; autoxidation; copper(II) catalysis; amino acids; protection; antioxidants; CHELATE CATALYZED OXIDATION; NEURODEGENERATIVE DISEASES; MOLECULAR OXYGEN; METAL-COMPLEXES; CUPRAC METHOD; ANTIOXIDANT; ION; ASPARTAME; KINETICS; SYSTEM